2014
DOI: 10.3923/ijb.2015.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Structures and Stomatal Ontogeny in Terminalia catappa L. (Combretaceae)

Abstract: A B S T R A C T Stomatal ontogeny and epidermal characteristics of Terminalia catappa L., an important tropical economic plant, were studied and described. The central portions of cotyledonary and mature leaves were peeled, stained with acetocarmin, 1% safranin and fast green stains as required, mounted on microscope slides and observed under Olympus photomicroscope for stomata ontogeny and developmental stages. The cells of the epidermis of the species are polygonal, isodiametric or elongated in various direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…On the other hand, considering the epidermal features on the adaxial layer, Ficus exasperata is distanced from F. muscuso and F. thonningii by having hypostomatic leaves. There exist studies [23][24][25][26][27][28] in which the positioning of stomata on the epidermal layer was used to delimit the taxa of plants. However, there is presently scarce information according to the literature on the discrimination of Ficus species based on the positioning of stomata but there is replete information on other epidermal indices such as stomatal types and epidermal cell shape [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, considering the epidermal features on the adaxial layer, Ficus exasperata is distanced from F. muscuso and F. thonningii by having hypostomatic leaves. There exist studies [23][24][25][26][27][28] in which the positioning of stomata on the epidermal layer was used to delimit the taxa of plants. However, there is presently scarce information according to the literature on the discrimination of Ficus species based on the positioning of stomata but there is replete information on other epidermal indices such as stomatal types and epidermal cell shape [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was different from the results of Des et al (2021) who reported that in Ketapang leaves, stomata were only found on the abaxial surface, therefore they were classified as hypostomatic type. However, Ekeke & Agbagwa (2015) reported that the distribution of stomata on Ketapang leaves between cotyledon leaves and mature leaves was different. In cotyledon leaves, stomata were found on both adaxial and abaxial surfaces while in mature leaves, stomata were found only on the abaxial surface.…”
Section: Total Of Individuals 138mentioning
confidence: 99%
“…Paracytic stomata were also found in Pucuk Merah leaves (Myrtaceae). Paracytic stomata were defined as possessing one or more pairs of lateral subsidiary cells oriented parallel with the guard cells (Ekeke & Agbagwa, 2015). Anomocytic stomata were found on several other species leaf such as Mahogany, Glodogan Tiang, Ketapang, Ketapang Kencana, Nyamplung, Bungur, Beringin, Ketapang Biola Cantik, and Sawo Kecik.…”
Section: Total Of Individuals 138mentioning
confidence: 99%
See 2 more Smart Citations